Quantification of hepatitis B virus (HBV) DNA and HBV genotyping simultaneously in plasma using real-time polymerase chain reaction - Woottichai Khamduang; Amonrat Pota; Wanvisa Khamlasai; Sayamon Hongjaisee; Nicole Ngo-Giang-Huong; Wasna Sirirungsi (Journal of Associated Medical Sciences, 2018)
Background: in Thailand, an estimated three million people are chronically infected with hepatitis B virus (HBV), mostly with genotypes C and B. Level of HBV replication as measured by quantification of HBV DNA in blood is crucial for management of chronic hepatitis B.  However, HBV DNA measurement is not widely used due to limited availability and high cost of the test.